Evaluation of Lumax for preemergence weed control in maize in Nigeria - Chikoye, David; Lum, A.F.; Ekeleme, F.; Udensi, U.E. (Informa UK Limited, 2009)
The eﬃcacy of various herbicides against weeds of maize was studied in ﬁeld trials at Ibadan, Nigeria in 2003 and 2004. Theformulationswereatrazine(Gesaprim1 90WDGat3.5 kga.i.ha71 and Rhonazine1 80WP at3.0 kga.i.ha71),a mixture of atrazine and metolachlor (Primextra1 GoldTM 660 SC at 4.0 kg a.i. ha71 and Primextra1 500 FW at 2.5 kg a.i. ha71), and a mixture of mesotrione, S-metolachlor and atrazine (Lumax1 at ﬁve rates: 1.88–2.96 kg a.i. ha71). Unweeded and hoe-weeded treatments were controls. Lumax1 at all rates, Rhonazine1 at 3.0 kg a.i. ha71, and Primextra1 at2.5 kga.i.ha71 controlledsedges,Commelinabenghalensis,and Puerariaphaseoloides as eﬀectively as the weededcontrol(95–100%).Weeddensityandbiomassweresigniﬁcantlyreducedandmaizeyieldincreasedby12–22%. Thehighestyieldwasintreatmentswith2.15 7 2.96 kga.i.ha71ofLumax1and3.5 kga.i.ha71ofGesaprim1,andthe weeded control. Lumax1 is more eﬀective for weed control at lower rates than the previously used formulations.